Emotional intelligence and university students’ happiness: The mediating role of basic psychological needs’ satisfaction - Vasiou, Aikaterini; Vasilaki, Eleni; Mastrothanasis, Konstantinos; Galanaki, Evangelia (Psychology International, 2024)
Given the increasing importance of adjusting to university life and achieving happiness, identifying the effective role of emotional intelligence and psychological needs’ satisfaction in enhancing students’ well-being is crucial. This study investigated the relation between emotional intelligence, psychological need satisfaction, and university students’ happiness. Data were collected from 205 university students (mean age: 23.35; predominantly female) at the University of Crete. Participants completed the Emotional Intelligence Scale, the Oxford Happiness Questionnaire, and the Basic Psychological Needs Satisfaction Scale. The analysis began with a correlation matrix to explore preliminary relations among the key variables. A multiple-linear regression analysis was then conducted to predict happiness levels based on observed correlations. Following this, a multiple-mediation analysis examined how emotional intelligence affects happiness through psychological needs satisfaction. The results indicated a positive association between emotional intelligence and happiness, with psychological needs’ satisfaction also positively correlating with happiness. Specifically, the use and regulation of emotion, competence, and autonomy significantly predicted happiness. Path analysis revealed that emotional intelligence indirectly influences happiness, particularly through competence. The results indicate that high emotional intelligence, through the satisfaction of basic psychological needs, is significantly associated with university students’ happiness. The study suggests that institutions should guide students in emotional intelligence and competence to increase happiness during their studies.